Exploring Attitudes and Attitude Change In Settings of Violent Conflict - McFarlane, Denise J. (My University, 2003)
This study is exploratory research which took place in the Balkans, primarily in Kosovo investigating a social psychological hypothesis that persons who have been exposed to violent conflict and/or atrocity resulting from or exacerbated by physical, cultural, and/or moral distancing are conditioned to conflict-created negative attitudes. Such attitudes as fear, suspicion, anger, and/or hatred toward those who are associated with the perpetrators of violence solely due to a common religion, nationality, ethnicity, and/or cultural heritage could perpetuate violent behaviors toward those in that ethnic group. It further considers what approaches might positively recondition such attitudes. Considered are the existing attitudes and lack of interaction between those in the conflicted ethnic groups, how the attitudes are conflict-related, and how they might be changed to awareness of commonalities, tolerance, and alternative perspectives. Additionally considered are how these attitudes can be affected by an attitude reconditioning process and attitude-focused programs including the use of mediation to facilitate communication and ease tension. The statistical data and interview comments found a significant rise in the levels of fear, suspicion, anger and hatred among those interviewed, including a significant connection of those attitudes to the ethnicity of the associated group rather than any specific action by individuals. A significant difference in attitude was also found in lower levels of anger in younger groups. Two other attitudes were found which hadn't been anticipated, aversion and scorn, however these appear to be significant in their effect on the individuals in this environment.